Estudo de águas subsuperficiais em áreas de contribuição de fontes naturais suportadas por Sedimentos Cenozóicos e da Formação Itaqueri, na região de São Carlos - SP - Basilio, Thamiris Cristina Costa (Universidade Federal de São Carlos, 2019)
The water crisis is a hotly debated issue in recent years, especially as regards the effects of globalization, both on the interference of climate change directly on recharge and on the disorderly increase of the urban environment that directly affects the availability of water for domestic consumption, and industrial. These climate changes alter pluviometric regimes and volumes, evapotranspiration, the recharge process of aquifers, and river flows. Deforestation and paving of recharge areas are the result of urbanization and the advancement of agricultural production, leading to increased waterproofing of the soil and thus affecting the infiltration and storage of groundwater. The objective was to fill some gaps in the literature, in relation to the studies that investigate the water refills, using a bibliometric mapping and geological-geotechnical detail mapping, aiming the monitoring of water recharge zones in the region north of the municipality of São Carlos, SP. In order to do so, the monitoring of free aquifer of the microbasin was carried out by means of frequent measurements of the static levels of 4 monitoring wells for the subsequent application of the Water Tabel Fluctuation (WTF) method that verified an annual recharge of 1338.8mm, lower value to the previous years, representing an average of 16-36% of all direct annual recharge of the microbasin. In addition, a multitemporal analysis of the soil cover type was done in this study, demonstrating the problems generated by the increase of the percentage of soil exposed in regions of springs, increasing, consequently, the surface runoff and reducing the infiltration. It is concluded that the monitoring of the recharge of water has been satisfactory and that stricter measures in the management of water resources must be taken so that future generations do not suffer from water crises in the region. In addition, urban sprawl in the study area may directly interfere with this decrease in surface recharge.
Study of subsurface waters in contribution areas of natural sources supported by Cenozoic Sediments and Itaqueri Formation, in the region of São Carlos - SP
Keywords: Crise hídrica; Expansão urbana; Impermeabilização do solo; WTF; Nascentes; Recarga de águas superficiais; Water crisis; Urban expansion; Soil waterproofing; Springs; Recharge of groundwater; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA